2016
DOI: 10.1007/s13197-016-2291-z
|View full text |Cite
|
Sign up to set email alerts
|

Implication of processing and differential blending on quality characteristics in nutritionally enriched ketchup (Nutri-Ketchup) from acerola and tomato

Abstract: The present study was focused on the development of nutritionally enriched ketchup (Nutri-ketchup) from acerola and tomato and evaluation of the effect of blending and processing on physicochemical characteristics, phytonutrients retention, antioxidant activity and sensorial quality. Acerola and tomato pulps blended in various ratios viz. 100:0, 75:25, 50:50, 25:75 and 0:100 were used for the preparation of five formulations of ketchup and compared with commercially available tomato ketchup. The retention of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
2
6
0
3
Order By: Relevance
“…The above denotes the effect of the atmosphere on microbial growth, indicating greater development in atmospheres with higher oxygen contents. This effect was also reported by Baskaran et al (2015) on minimally processed onions stored in a modified atmosphere, suggesting an effect of the composition of the gas on growth of these microorganisms on the vegetables.…”
Section: Microbiological Analysissupporting
confidence: 76%
“…The above denotes the effect of the atmosphere on microbial growth, indicating greater development in atmospheres with higher oxygen contents. This effect was also reported by Baskaran et al (2015) on minimally processed onions stored in a modified atmosphere, suggesting an effect of the composition of the gas on growth of these microorganisms on the vegetables.…”
Section: Microbiological Analysissupporting
confidence: 76%
“…Viscosity of ketchup determines the rheological properties, which is also dependent on temperature of the storage condition. As such, the use of stable gelling agent such as date pits will ensure stability of the tomato ketchup in different storage conditions and the ability to avoid challenges such as phase separation, loss of consistency, and consumer unacceptability (Koocheki et al, 2009 andPrakash, et al, 2016). The purpose of this research is to determine the rheological, chemical, and organoleptic properties of ketchup enriched with khalas date pits as source of dietary fiber.…”
Section: Introductionmentioning
confidence: 99%
“…However, as ascorbic acid is highly unstable, its loss incurred in value added products during processing should also be considered. Our group showed a * 18-29% retention of ascorbic acid in various ketchup formulations developed from acerola and tomato (Prakash et al 2016). In another study, Moreira et al (2009) reported a 6-15% loss of ascorbic during spray drying of acerola pomace extract.…”
Section: Ascorbic Acidmentioning
confidence: 65%
“…The anthocyanins content in commercial pulps were around 2.7 mg/100 g cyanidin-3glucoside while the content in crushed and squeezed juices ranged around 46.9-52.3 mg/L cyanidin-3-glucoside. The phenolic content in acerola pulp and juices is higher than the fruits like caqui, pineapple, mango, guayaba, etc., but the anthocyanins content are lower than other fruit juices rich in anthocyanins like strawberries or blood oranges (Mezadri et al 2008) Prakash et al (2016 developed ketchup from different blended proportions of acerola and tomato and found varied retention of color after blending and blending.…”
Section: Ascorbic Acidmentioning
confidence: 99%